Multiperturbation analysis of distributed neural networks: The case of spatial neglect - Kaufman, Alon (Hum Brain Mapp, 2009)
This study assesses the feasibility of using a multiperturbation analysis (MPA) approach for lesion‐symptom mapping. We analyze the relative contribution of damage in different brain regions to the expression of spatial neglect, as revealed in line‐bisection performance. The data set comprised of normalized lesion information and bisection test results from 23 first‐event right‐hemisphere stroke patients. Obtaining quantitative measures of task relevance for different regions of interest (ROIs), the following ROIs were found to be the most contributing: the supramarginal and angular gyri of the inferior parietal lobule, the superior parietal lobule, the anterior part of the temporo‐parietal junction connecting the superior temporal and supramarginal gyri, and the thalamus. MPA is likely to play an important role in elucidating the anatomical substrate of complex functions. Hum Brain Mapp, 2009. © 2009 Wiley‐Liss, Inc.